Hypermethylation of SOX1 and HOXA9 Genes Is Associated with Clinicopathologic Characteristics of Non-Small Cell Lung Cancer Patients - Milica Kontić; Mihailo Stjepanović; Filip Marković (Current Issues in Molecular Biology, 2025)
DNA methylation changes, especially hypermethylation of SOX1 and HOXA9, may serve as biomarkers for diagnosis and prognosis in non-small cell lung carcinoma (NSCLC). This study analyzed the methylation status of SOX1 and HOXA9 in 63 primary NSCLC tumor samples, corresponding normal lung tissues, and circulating blood, using bisulfite pyrosequencing. The relationship between methylation patterns and clinicopathologic features was also explored. SOX1 and HOXA9 promoter methylation levels were significantly higher in tumor tissues compared to normal lung tissues and blood samples. Histological subtypes influenced methylation patterns, with squamous cell carcinomas (SCC) showing higher hypermethylation rates at both loci compared to other NSCLC subtypes. HOXA9 hypermethylation was associated with advanced tumor stage (stages II and III). Gender and smoking status did not correlate with methylation status. These findings highlight the cancer-specific nature of SOX1 and HOXA9 hypermethylation in NSCLC. Further investigation into demographic and molecular factors influencing methylation could enhance the clinical utility of SOX1 and HOXA9 in NSCLC diagnosis and management.